4CPS-089 Retreatment of patients with hepatitis C virus infection after virological failure to direct-acting antivirals. (March 2019) - Burgui, C; Juanbeltz, R; Castilla, J; Larrayoz, B; Sarobe, M; Perez, A; Aguinaga, A; Zozaya, Jm; Gracia-Ruiz de Alda, M; San Miguel, R
Abstract : Background: New oral interferon-free direct-acting antivirals (DAAs) have demonstrated high effectiveness treating chronic hepatitis C. However, a few patients still do not achieve sustained virological response (SVR). Purpose: To describe those patients treated with new interferon-free DAAs for chronic hepatitis C, who had virological failure (VF), and their retreatment outcomes. Material and methods: A retrospective observational study for patients with VF to DAAs who were retreated in a reference hospital from 2015 to September 2018. Variables analysed: sex, age, genotype, HIV co-infection, METAVIR score (F0–F4), DAA treatment, retreatment therapy, presence of resistance-associated substitutions (RASs) and SVR 12 weeks after the end of retreatment (SVR12). Results: Twenty-four of 1356 patients treated for hepatitis C virus with interferon-free DAAs therapies had a VF (1.8%). Seventeen were retreated (seven are pending). Median age was 51 years (36–60), 88% male. Two patients were HIV co-infected. Genotypes: G1a (n=6); G1b (n=5); G2 (n=1); G3 (n=4); and G4 (n=1). Based on METAVIR score: F4 (n=6); F3 (n=3); F2 (n=4); and F0–F1 (n=4). Previous DAAs treatments were: ombitasvir/paritaprevir/ritonavir/dasabuvir ±ribavirin (RBV) (n=7); ledipasvir/sofosbuvir (SOF) ±RBV (n=3); daclatasvir/SOF ±RBV (n=2); velpatasvir/SOF (n=1); glecaprevir/pibrentasvir (n=1); elbasvir/grazoprevir (n=1); SOF +RBV (n=1); and ombitasvir/paritaprevir/ritonavir+RBV (n=1). Patients retreatment: SOF/velpatasvir/voxilaprevir (n=9); elbasvir/grazoprevir/SOF ±RBV (n=5); daclatasvir/SOF ±RBV (n=1); velpatasvir/SOF +RBV (n=1); and simeprevir/SOF +RBV (n=1). Fifteen patients (88%) were studied for RASs: four had only an available post-treatment sample and all presented a RAS related to the first DAA treatment; three had RASs at baseline and post-treatment samples; and in eight patients the RAS was only present in a post-treatment sample. SVR12 figures were available for 14 patients: 13 reached a SVR and one rebounded (three patients did not yet have analysis). Per protocol analysis, the rate of SVR was 93% for those retreatments. The patient that rebounded was G3, F4, co-infected, received at first daclatasvir/SOF +RBV during 24 weeks and was retreated with velpatasvir/SOF +RBV during 24 weeks. Conclusion: Although only a reduced proportion of treated patients did not achieve a SVR with DAA combinations, retreatment with a new strategy reached 93% of SVR. References and/or acknowledgements: EIPT-VHC project funded by the Spanish Ministry of Health and Carlos III Institute of Health. No conflict of interest.